Probiotic supplementation promotes a reduction in T‐cell activation, an increase in Th17 frequencies, and a recovery of intestinal epithelium integrity and mitochondrial morphology in ART‐treated HIV‐1‐positive patients. Issue 3 (20th April 2017) - d'Ettorre, Gabriella; Rossi, Giacomo; Scagnolari, Carolina; Andreotti, Mauro; Giustini, Noemi; Serafino, Sara; Schietroma, Ivan; Scheri, Giuseppe Corano; Fard, Saeid Najafi; Trinchieri, Vito; Mastromarino, Paola; Selvaggi, Carla; et al.
Abstract: Introduction: HIV infection is characterized by a persistent immune activation associated to a compromised gut barrier immunity and alterations in the profile of the fecal flora linked with the progression of inflammatory symptoms. The effects of high concentration multistrain probiotic (Vivomixx®, Viale del Policlinico 155, Rome, Italy in EU; Visbiome®, Dupont, Madison, Wisconsin in USA) on several aspects of intestinal immunity in ART‐experienced HIV‐1 patients was evaluated. Methods: A sub‐study of a longitudinal pilot study was performed in HIV‐1 patients who received the probiotic supplement twice a day for 6 months (T6). T‐cell activation and CD4+ and CD8+ T‐cell subsets expressing IFNγ (Th1, Tc1) or IL‐17A (Th17, Tc17) were stained by cytoflorimetric analysis. Histological and immunohistochemical analyses were performed on intestinal biopsies while enterocytes apoptosis index was determined by TUNEL assay. Results: A reduction in the frequencies of CD4 + and CD8 + T‐cell subsets, expressing CD38 +, HLA‐DR +, or both, and an increase in the percentage of Th17 cell subsets, especially those with central or effector memory phenotype, was recorded in the peripheral blood and in gut‐associated lymphoid tissue (GALT) after probiotic intervention. Conversely, Tc1 and Tc17 levels remained substantially unchanged at T6, while Th1 cell subsets increase in the GALT. Probiotic supplementation was also associated to a recovery of the integrity of the gut epithelial barrier, a reduction of both intraepithelial lymphocytes density and enterocyte apoptosis and, an improvement of mitochondrial morphology sustained in part by a modulation of heat shock protein 60. Conclusions: These findings highlight the potential beneficial effects of probiotic supplementation for the reconstitution of physical and immunological integrity of the mucosal intestinal barrier in ART‐treated HIV‐1‐positive patients. Abstract : (i) Probiotic supplementation causes a reduction in the frequencies of CD4+ and CD8+ T‐cell subsets, expressing CD38+, HLA‐DR+, or both, in HIV‐1 patients; (ii) probiotics intervention leads to an increase of the frequency of Th17 cell subsets (central memory and effector memory) in HIV‐1 patients; (iii) probiotic supplementation was associated to a reduction of diffuse interstitial inflammatory infiltrate, and an increase in the number and area of the GALT structures associated to the mucosa in HIV‐1 patients; (iv) probiotic supplementation leads to a reduction of both IELs density and enterocytes death via apoptosis in HIV‐1 patients; (v) probiotics improves mitochondrial morphology through a localization of mitochondrial chaperonin, HPS60, from cytosol to mitochondrial compartment in HIV‐1 patients.